1981
DOI: 10.1002/jat.2550010405
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury poisoning in the Iraqi suckling infant: A longitudinal study over five years

Abstract: In a five-year longitudinal study of mothers and infants exposed to methylmercury during the Iraq epidemic of 1972, the frequencies of signs and symptoms exhibited by the mothers were typical of methylmercury poisoning. When blood concentrations of mercury are corrected to 1 March 1972, mothers with the most severe signs and symptoms had an average blood mercury concentration significantly higher (p less than 0.01) than either the milder or asymptomatic groups. Analytical data indicate that the predominant rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…Stern (1993) considered the available human and animal study data addressing developmental endpoints and suggested that the weight of evidence indicated the reference dose ( RfD ) to be 0.07 g /kg /day. With the understanding that the fetus and infant are more sensitive to adverse effects from methylmercury exposure, Gilbert and Grant -Webster (1995 ) used the Iraq episode data (Amin -Zaki et al, 1981;Marsh et al, 1987 ), supported by data on neurobehavioral effects in animals, to develop an RfD range of 0.025 to 0.06 g/kg/ day. Zelikoff et al ( 1995 ) considered various approaches for establishing an RfD based on prenatal methylmercury exposure effects in small mammals, nonhuman primates and humans.…”
Section: Results /Discussionmentioning
confidence: 99%
“…Stern (1993) considered the available human and animal study data addressing developmental endpoints and suggested that the weight of evidence indicated the reference dose ( RfD ) to be 0.07 g /kg /day. With the understanding that the fetus and infant are more sensitive to adverse effects from methylmercury exposure, Gilbert and Grant -Webster (1995 ) used the Iraq episode data (Amin -Zaki et al, 1981;Marsh et al, 1987 ), supported by data on neurobehavioral effects in animals, to develop an RfD range of 0.025 to 0.06 g/kg/ day. Zelikoff et al ( 1995 ) considered various approaches for establishing an RfD based on prenatal methylmercury exposure effects in small mammals, nonhuman primates and humans.…”
Section: Results /Discussionmentioning
confidence: 99%
“…There were also some fetal cases, in which the mothers ate contaminated bread during pregnancy thereby exposing the fetuses to methylmercury in utero 24) . After birth, the infants were examined for physical and mental development [25][26][27] . The developmental data were statistically analyzed to establish a dose-response relationship between the exposure doses and the effects (developmental retardation).…”
Section: Methylmercury Poisoning In Iraqmentioning
confidence: 99%
“…As mentioned above, in the Iraqi outbreak fetal cases were examined more closely [24][25][26][27]48) . A group of mother and infant pairs were examined for the delay in developmental milestones such as walking and talking and the mothers' exposure to mercury, with the hair mercury content of each mother analyzed to determine the peak mercury concentration during pregnancy.…”
Section: Effects Of In Utero Methylmercury Exposurementioning
confidence: 99%
“…Its toxicity has been known for centuries (4) and multiple episodes of poisoning in children by both inorganic and organic mercury have been reported (5,6). The organic forms of mercury are particularly neurotoxic (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Both prenatal and postnatal exposure to MeHg can adversely affect the central nervous system, but it appears to be most neurotoxic prenatally when the brain is developing rapidly.…”
Section: Human Effects Of Methylmercurymentioning
confidence: 99%